2018
DOI: 10.1038/s41439-018-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel MLH1 mutation in a Japanese family with Lynch syndrome associated with small bowel cancer

Abstract: Lynch syndrome is a genetic disorder related to cancer predisposition, including colorectal cancer, endometrial cancer, and ovarian cancer. Germline mutations in mismatch repair genes, including MLH1, MSH2, MSH6, and PMS2, are responsible for this condition. Cancer tissue specimens resected from small bowel adenocarcinoma in a Japanese patient showed decreased expression of MLH1 and PMS2 by immunohistochemistry testing. Finally, a novel MLH1 mutation, c.1833dup, was identified in this patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Based on the InSIGHT five-tier system [38], up till now 1344 MLH1 variants have been registered for LS associated CRCs [39]. According to HGMD database, 1069 different types of mutations in different exons of MLH1 has been reported (Figure 6A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the InSIGHT five-tier system [38], up till now 1344 MLH1 variants have been registered for LS associated CRCs [39]. According to HGMD database, 1069 different types of mutations in different exons of MLH1 has been reported (Figure 6A,B).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found a heterozygous missense mutation Furthermore, in the InSiGHT database, more than 1344 MLH1 variants have been registered for LS or other associated disorders [19]. Twelve missense mutations in exon 18 of MLH1 have been classified as class 5 (pathogenic) based on the 5-tier system proposed by InSiGHT [20].…”
Section: Discussionmentioning
confidence: 89%
“…In CRC, the classic model of carcinogenesis is the adenoma carcinoma sequence [117][118][119][120][121]. Based on this scheme, malignant CRC cells have the capacity to accumulate a number of immunogenic mutations and become a potential target for immunotherapy, even though they might remain less immunogenic than melanoma or NSCLC [122].…”
Section: Mutational Burden and Neoantigen Densitymentioning
confidence: 99%